PROBLEMATIKA PENGEMBANGAN KURIKULUM DI LEMBAGA PENDIDIKAN ISLAM : TINJAUAN EPISTIMOLOGI - Muhammad Ilyas Junaidi Addahil (STAI Ma'had Aly Al-Hikam Malang, 2019)
This research attempts to describe the problems of Islamic religious education curriculum in Indonesia. There are many problems of the curriculum of Islamic religious education in Indonesia such as the duration of learning, textbooks, conformism curriculum and human resources, change of curriculum, curriculum design, pendektean/ learning methods, facilities and infrastructure, the absence of a draft formal assessment of affective from the government, the assessment tool affective difficult to develop.The methods used in this research is using descriptive analysis method. While the analysis of the data used by the author is using content analysis that describes the contents of the text of some of the sources are accurate. From the analysis of the data that has been concluded by the authors showed that many of the problems of Islamic religious education curriculum in Indonesia. problematics of Islamic religious education curriculum in Indonesia should be evaluated, with evaluation of the problems of Islamic religious education curriculum in Indonesia is expected that there will be a revamping of the curriculum so that the education system in Indonesia mainly Islamic religious education can be done well.